1986
DOI: 10.1083/jcb.102.2.587
|View full text |Cite
|
Sign up to set email alerts
|

A unique heparan sulfate in the nuclei of hepatocytes: structural changes with the growth state of the cells.

Abstract: Abstract. Growing and confluent cultures of a rat hepatocyte cell line were labeled with 35SO42-and the heparan sulfate in the culture medium, the pericellular matrix, the nucleus, the nuclear outer membrane, and the remaining cytoplasmic pool was purified by DEAE-cellulose chromatography. The heparan sulfate in all pools from the confluent cells was bound more strongly on the DEAE-cellulose column than the corresponding pools from the growing cells. Gel filtration of each pool before and after ~-elimination s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
143
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(155 citation statements)
references
References 72 publications
10
143
0
2
Order By: Relevance
“…We then examined whether SST0001 was having a direct effect on HAT activity. This is an important question because SST0001 is composed of a chemically modified heparin (26), and studies have shown that when heparin is added to cells, it can be transported to the nucleus (17,27). Because heparin can inhibit HAT activity (15), it is possible that when SST0001 is added to cells it is transported to the nucleus where it directly inhibits HAT activ-FIGURE 1.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined whether SST0001 was having a direct effect on HAT activity. This is an important question because SST0001 is composed of a chemically modified heparin (26), and studies have shown that when heparin is added to cells, it can be transported to the nucleus (17,27). Because heparin can inhibit HAT activity (15), it is possible that when SST0001 is added to cells it is transported to the nucleus where it directly inhibits HAT activ-FIGURE 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 2-Osulfated glucuronic acid residue is a rare constituent of HS, and was found in HS isolated from the adult human cerebral cortex, a nuclear fraction from hepatocytes, HS from bovine kidney, and heparin from porcine intestines (41)(42)(43). This residue is synthesized by HS 2-O-sulfotransferase, although the enzyme preferably generates 2-O-sulfated iduronic acid (IdoUA2S) (44).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported the presence of HS chains in the nucleus of various cell types [5][6][7][39][40][41] and demonstrated that HSPGs may regulate the internalization and nuclear uptake of FGF-1 and FGF-2. [7][8][9] It was also suggested that a correlation exists between nuclear localization of HS and the growth rate of hepatoma cells, and that both glypican and biglycan participate in the regulation of C6 glioma cell proliferation and survival through a direct involvement of HSPGs in nuclear processes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 HSPGs thus influence a variety of normal and pathological processes involving cell adhesion, migration and invasion. [1][2][3][4] Although presence of HSPGs in the cell nucleus has long been reported, [5][6][7] their biological significance was not clearly elucidated. Several studies have demonstrated the involvement of HS in internalization and nuclear uptake of FGF-1 and FGF-2.…”
mentioning
confidence: 99%